The Role of ROA in Mediating DER, Current Ratio, and TATO on Firm Value - Widyakto, Adhi; Pradiptya, Adhi; Andriani Kusumawati, Citra; Fresiliasari, Oktavie (Jurnal Penelitian Ekonomi dan Bisnis, 2024)
Abstract______________________________________________________This research aims to obtain empirical evidence on the effect of debt equity ratio, current ratio and toral asset turnover on firm value through return on assets. This research was quantitative one with its secondary data obtained from annual financial statements published by companies. Its population included food and beverage companies registered in the Indonesian Stock Exchange in 2017-2022. samples were taken using purposive sampling where 52 companies were obtained. The collected data were then processed using e-views program. Debt equity ratio had no effect on return on assets. Current ratio negatively and significantly affected return on asset. Total Asset Turnover positively and significantly affected return on asset. Debt Equity Ratio negatively and affected considerably price to book value. Current Ratio did not affect price to book value. Both total asset turnover and return on assets positively and significantly affected price to book value. Debt equity ratio affected price to book value via return on assets. Current ratio and total asset turnover had no effect on price to book value via return on asset. Sales growth and total asset turnover had no effect on price to book value via the intervening variable, i.e., return on assets. For this reason, future researchers are recommended to add more variables presumably capable of serving as an intervening variable such as return on equity. Since the samples used only included Food and Beverages companies registered in IDX 2017-2022, future research is suggested to expand the samples to allow them to capture the effects of variables that they will study. This research made some contribution to financial management literature. The research showed different findings from the previous one, allowing them to be used as something new regarding the factors affecting profitability and firm value. The research found that total asset turnover and return on assets positively and significantly affected price to book value. Therefore, it is important for managers to pay closer attention to it to increase their firm values.   debt equity ratio, current ratio, total asset turnover, return on assets, price to book value. Keywords debt equity ratio, current ratio, total asset turnover, return on asset, price to book value